Dampak PLTA Poso Energi terhadap Ekosistem Perairan Danau Poso di Sulawesi Tengah - Ari Wirachandra; Erny Poedjirahajoe; Ris Hadi Purwanto (Faculty of Forestry Universitas Gadjah Mada, 2024)
The Poso Energy Hydropower Plant (PLTA) operation and various industrial, agricultural, and domestic waste disposal activities could impact the Lake Poso aquatic ecosystem. However, no documented reports have been detailing the impact of the PLTA. Therefore, this research aimed to analyze the characteristics of the Lake Poso aquatic ecosystem, focusing on physical (TSS, odor, color, turbidity), chemical (pH, DO, BOD, COD, NO3-N, total phosphate), and biological (fecal coliform, plankton diversity) parameters. Water samples were collected at six points in the area before, surrounding, and after the PLTA from July to September 2022. Analyzing the sample data using the analysis of variance (ANOVA) revealed significant differences in physical, chemical, and biological parameters among the six sample points. Additionally, the results showed that the PLTA impacted the characteristics of the Lake Poso aquatic ecosystem, particularly affecting parameters such as TSS, DO, COD, NO3-N, color, and total phosphate. An environmentally sound waste management strategy is urgently needed to support Lake Poso's aquatic ecosystem conservation.